ANALISIS THREE FACTOR FAMA AND FRENCH MODEL DAN CAPITAL ASSET PRICING MODEL - Rakhmawati, Ully; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out whether Three Factor Fama and French and Capital Asset Pricing Model can explain the expected stock return level and to find out which asset pricing model is the best in explaining the estimation level of the expected stock return in Indonesia Stock Exchange.The population is all companies which are listed in 50 large capital companies in Fact Book in Indonesia Stock Exchange in 2007-2013 periods. 39 companies have been selected as samples by using purposive sampling and the analysis technique has been done by using multiple regressions analysis.The result of the test shows that simultaneously market risk, small minus big, high minus low and debt to equity ratio have influence to the stock portfolio. This condition indicates that the research model is feasible for the following analysis. The result of partial test shows that high minus low variable can give more explanation of stock portfolio than market risk, small minus big and debt to equity ratio variables. This result can be seen from the significance level of high minus low to the stock portfolio.Keywords:Market Risk, Small Minus Big, High Minus Low, Debt to Equity Ratio, Stock Portfolio.